2019
DOI: 10.1038/s41467-019-12926-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution and biogeographic spread in a colorectal cancer

Abstract: How and when tumoral clones start spreading to surrounding and distant tissues is currently unclear. Here we leveraged a model-based evolutionary framework to investigate the demographic and biogeographic history of a colorectal cancer. Our analyses strongly support an early monoclonal metastatic colonization, followed by a rapid population expansion at both primary and secondary sites. Moreover, we infer a hematogenous metastatic spread under positive selection, plus the return of some tumoral cells from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…In this case the primary was not resected as deemed not clinically active, providing an opportunity for concomitant sampling of primary and metastatic deposits. Reconstruction of the metastatic cascade revealed that early monoclonal seeding was the dominant pattern of metastatic spread, as previously reported in colorectal cancer 20,23 , with evidence of polyclonal seeding restricted to one liver and one ovary sample. In the second patient, treated with standard systemic agents as well as targeted therapy, monoclonal seeding was also dominant, with a pattern of early metastatic seeding to lung and liver and a single (monophyletic) metastatic clone invading the para-aortic lymph nodes.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In this case the primary was not resected as deemed not clinically active, providing an opportunity for concomitant sampling of primary and metastatic deposits. Reconstruction of the metastatic cascade revealed that early monoclonal seeding was the dominant pattern of metastatic spread, as previously reported in colorectal cancer 20,23 , with evidence of polyclonal seeding restricted to one liver and one ovary sample. In the second patient, treated with standard systemic agents as well as targeted therapy, monoclonal seeding was also dominant, with a pattern of early metastatic seeding to lung and liver and a single (monophyletic) metastatic clone invading the para-aortic lymph nodes.…”
Section: Discussionsupporting
confidence: 70%
“…Lymph node dissemination also occurred early but independently. Early dissemination has been documented before both in breast 22 and colon cancer 20,23 . Hence, dissemination to the large majority of sites was consistent with monoclonal seeding (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An especially promising direction for future research is in combining clonal diversity measurements with information about evolutionary processes, such as the pervasiveness of selective sweeps in a given tumour type across individuals or in a particular tumour within an individual. Although it is generally infeasible to infer a complete history of clonal turnover, genomic data from even a single timepoint can potentially be used to infer the strength of selection, time since the most recent common ancestor, and rate of demographic expansion (Williams et al, 2018;Alves et al, 2019). Future work should employ multi-variable statistical models that incorporate such information about tumour evolution, ecology and demography (Maley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tumor multi-region sequencing studies of colorectal cancer have demonstrated ITH [6][7][8][9][10][11][12][13]. This multiregional sequencing approach, sequencing DNA samples from geographically separated regions of a single tumor, explores ITH and cancer evolution.…”
Section: Introductionmentioning
confidence: 99%